Conteúdo energético e emissões de CO2 em coberturas verdes, de telha cerâmica e de fibrocimento: estudo de caso - Pereira, Marcos Fabricio Benedetti (2014)
CO2 is one of the main gases accountable for the increment of the greenhouse effect, of climate changes, and of environmental degradation arising from this ecological unbalance. Civil construction is one of the main sources of CO2 emissions, using construction techniques that are more sustainable can contribute to the reduction of those emissions. Furthermore, the energy content of materials must be taken into account as well due to the fact that the consumption of petroleum by-products increases the CO2 indexes in the atmosphere. It becomes then clear that the less energy is consumed, even those renewable, the less environmental impact there is. Thus, it is indispensable to analyse not only the emissions of CO2 but also the energy content of materials used in three roofing technologies under scrutiny in this research: green roofs, fibre cement, and ceramic tiles. Green roofs are a sustainable alternative to be implemented in covering the top of buildings. This research, therefore, aims to compare the CO2 emission to the energy content of two green roof solutions and of two traditional coverage solutions in the pre-operational phase in the cities of Porto Alegre and Santa Maria, both in the state of Rio Grande do Sul. The method used to identify left from the layers and constituents in each green cover, and the raw materials used in traditional roofs, measuring how much material was used for each cover, analyzing all the material traversed by the means of transport, quantifying emissions CO2 and energy consumption of materials by processes fabrication them and finally to compare all results. Common belief is that green roofs have the potential to mitigate environmental damages, especially those caused by the civil construction sector concerning CO2 emissions and energy consumption in the pre-operational phase, just as advantages in the operational phase are described. Such hypothesis was confirmed for the tested cover. However, among the possibilities discussed below for closing the top of buildings, green roofs are the only technology capable of mitigating environmental damage, in particular, the emission of carbon dioxide, and provide an environmental service to the community carbon sequestration to throughout his life . Nonetheless, amongst the building coverage possibilities herein analysed, green roofs are the only technology capable of integrally mitigating environmental damages in a few years, especially the emission of carbon dioxide, and also the only technology capable of providing an environmental service to the collectivity of carbon sequestration to throughout his life.